REKONSTRUKSI BUDAYA PATRIARKI DALAM VISUALISASI SURGA (Analisis Historis-Linguistik) - Moh. Nailul Muna (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This study aims to reconstruct the depiction of heaven which has been closely related to patriarchal culture. This can be proven when the Qur'an touches on the word of hūr which is interpreted feministly as a reward for Muslim, but it is not accompanied by a picture of Muslimah. The case, in fact appearing the patriarchal dimension in the visualization of the Qur'an about eschatological verses. Furthermore, through several other portrayals, men always get more portions - not to say everything - as the object of discussion about the pleasures of heaven verses. In fact, the visualization used by the Qur'an still raises numerous meanings if reviewed through various perspectives, one of which is linguistic and historical analysis. Through the historical approach, it can be seen that the explanation of heaven's visualization is closely related to the things that the Arab Muslim population dreamed of at that time. While based on grammatical aspects, the use of words that generally have a chemistry, in the other hand can be understood neutrally which implies that the message is also directed at women. Because it is reviewed holistically in several other verses, it requires the existence of the unity in interpreting masculine verses, but intended in general. This study, as well as an effort to clarify the point of differentiation between Islamic values and Arabian culture.